DETERMINAN KEPUTUSAN PERUSAHAAN MELAKSANAKAN TRANSFER PRICING - Nurfadhilah; Dewi Rejeki (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2024)
This study aims to test and analyze the influence of Tax, Bonus Mechanism and Company Size on the company's decision to carry out Transfer Pricing. The research was conducted on Industrial Sector companies listed on the Indonesia Stock Exchange in 2018-2022. The sample determination method uses purposive sampling so that the sample used is 10 companies for five years. The technical analysis used in this study is descriptive statistics, classical assumption tests, multiple regression tests and hypothesis tests consisting of simultaneous tests, partial tests and determination coefficient tests conducted using SPSS 25 for windows.The results of the study show that simultaneously taxes, bonus mechanisms and company size have a negative effect on the company's decision to carry out transfer pricing. Partially, the bonus mechanism and company size have a negative effect on the company's decision to carry out transfer pricing, while taxes have no effect on the company's decision to carry out transfer pricing.